2017
DOI: 10.3892/mmr.2017.6123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers of intrahepatic cholangiocarcinoma via integrated analysis of mRNA and miRNA microarray data

Abstract: The present study aimed to identify potential therapeutic targets of intrahepatic cholangiocarcinoma (ICC) via integrated analysis of gene (transcript version) and microRNA (miRNA/miR) expression. The miRNA microarray dataset GSE32957 contained miRNA expression data from 16 ICC, 7 mixed type of combined hepatocellular-cholangiocarcinoma (CHC), 2 hepatic adenoma, 3 focal nodular hyperplasia (FNH) and 5 healthy liver tissue samples, and 2 cholangiocarcinoma cell lines. In addition, the mRNA microarray dataset GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Various studies have demonstrated that the miRNA class of non-coding RNAs participate in tumor progression through regulating a series of target genes involved in tumor proliferation and metastasis (24). dysregulated expression or function of miRNAs has been demonstrated in a series of malignancies, including ccA (25). For example, miR-142-5p was shown to decrease the expression of phosphatase and tensin homolog and promote the progression of ccA (26).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that the miRNA class of non-coding RNAs participate in tumor progression through regulating a series of target genes involved in tumor proliferation and metastasis (24). dysregulated expression or function of miRNAs has been demonstrated in a series of malignancies, including ccA (25). For example, miR-142-5p was shown to decrease the expression of phosphatase and tensin homolog and promote the progression of ccA (26).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been implicated in the pathogenesis of CCA 42 45 because upregulated miRNAs suggest an oncogenic role and downregulation of miRNAs may be suppressive, so dysregulated miRNAs are correlated with the adverse clinical features, diminished survival, and poor prognosis of CCA patients. 46 Selaru et al 36 proved that miR-21 was oncogenic by inhibiting PDCD4 and TIMP3 suppressor genes in the biliary tree. Wang et al 38 confirmed the functional and mechanistic links between miR-21 and tumor suppressor genes (such as PTPN14 and PTEN) in the pathogenesis of ICC, which influenced the proliferation and tumor progression in ICC.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of liver cancer, the global profile of alternative RNA splicing events indicates the existence of differential AS in HCC and iCCA compared to adjacent non-tumor liver tissue, affecting several hundred genes. This information has been proposed as a valuable tool to distinguish different types of liver cancer [ 2 , 38 ].…”
Section: Liver Cancer-associated Alterations In the Spliceosome Machinerymentioning
confidence: 99%